Impact Of Leadership Style On Job Satisfaction Of Administrative Staff Of Budidarma University Medan - Ikwan Lubis; AMH. Sihite; Edizal Hatmi; Ilhamsyah Ilhamsyah (Institute of Computer Science (IOCS), 2022)
The purpose of this study was to find out the Impact of Superior Leadership on job satisfaction of Administrative Staff at BUDI DARMA University, Medan and to analyze whether superior Leadership variables affect Employee Employee Satisfaction Administration (Case Study: BUDIDARMA University Medan), The Data Collection Method used in this study is to use questionnaires, The data analysis model used is simple Linear Regression analysis. Sampling uses the stratified random sampling method, which first classifies a population, Probability sampling, which is a sampling technique that provides equal opportunities for each element (member) of the population at once the sample.The results of research at BUDIDARMA University, in Medan showed that superior leadership variables have an impact on satisfaction that can affect administrative staff to improve their work, this shows that the level of job satisfaction of administrative staff has not been considered maximally by the management of the company.